Women's Rebellion in Khaled Hosseini's A Thousand Splendid Sun: A Marxist Approach - Meiyono, Pitoyo, Dr. M. Thoyibi, MS, Dr. Abdillah Nugroho. M.Hum (2016)
As one of the literary works, Khaled Hosseini's A Thousand Splendid Suns can be seen as the means to deliver the certain message to the society. The message can be considered as the author's struggle to find equality. Therefore this research investigates how the women rebellion is described in the novel and what indicators are stated as the women rebellion. This research belongs to a qualitative study, which uses two data sources. The primary data source is the novel A Thousand Splendid Suns itself meanwhile the secondary data sources are any literatures or previous studies related to the novel. The data from the data sources are collected in a sort of document as evidence. The findings show that; first, Hosseini describes the rebellion through the women characters that are subordinated by the men characters to show the oppression relationship. Second, the novel tells of the women's rebellion actions which are divided into the common rebellion and the radical one which can be analyzed in the frame of Marxist theory. The last, Hosseini writes the story from the women's point of view in order to raise the sympathy of the Afghan women.